Interaction Between Language and the Mind Through Translation: A Perspective from Profile/Base Organization - Wu, Qing (Meta, 2002)
AbstractProfile/base organization in cognitive linguistics emphasizes a hierarchy of salience imposed on construal by usage events of some concept. Shift in terms of profile/base alignment is highly likely to occur in a cross-linguistic/cultural context. Granted two definitive features of translation, i.e., accountability of a TT to the ST’s textually-grounded intention, unless the TT has an otherwise stated intention, and systematicity attained within the TT itself, whether the shift(s) in a translation are explainable and how fall within our concern. This paper has examined the profile/base organization in two Chinese translations of the opening paragraph of William Faulkner’s The Sound and The Fury, and attempted to locate the factors to account for the textual realization in the TTs as such.